Pemberdayaan Kelompok Wanita Tani Dalam Upaya Pencegahan Dan Pemberantasan Penyakit Demam Berdarah Dengue Di Desa Bengking Klaten - Chairil Hana Mustofa; Refi Refi; Salsabila Salsabila; Septi Septi; Shifangi Shifangi; Sri Subekti; Vemas Vemas; Wahyu Wahyu; Wahyu Wulanndari; Muchson Arrosyid (Universitas Muhammadiyah Klaten, 2025)
Dengue Hemorrhagic Fever (DHF) is a significant health problem in Bengking Village, Jatinom District, especially during the rainy season, triggered by low public awareness in eradicating mosquito nests. This community service activity aims to empower the Bengking Village Women Farmers Group (KWT) by increasing knowledge and practices of DHF prevention, especially through the use of family medicinal plants (TOGA) and the implementation of Mosquito Nest Eradication (PSN) 4M Plus. The implementation method includes situation surveys, interactive counseling, demonstrations of making innovative products (herbal drinks), and post-activity monitoring and evaluation. A total of 40 KWT members actively participated in this activity. The results of the pre-test and post-test showed a significant increase in participant knowledge regarding the dangers of DHF, the mosquito life cycle, symptoms, and prevention and treatment strategies. In addition, there was an increase in public interest in planting and utilizing TOGA as a promotive and preventive measure. The success of this program is proven by the community's commitment to carrying out environmental cleanliness movements and consuming herbal concoctions, which collectively are expected to reduce DHF incidents and improve the quality of public health in Bengking Village in a sustainable manner.